2008
DOI: 10.1183/09031936.00035108
|View full text |Cite
|
Sign up to set email alerts
|

Integrated PET/CT in the staging of nonsmall cell lung cancer: technical aspects and clinical integration

Abstract: Lung cancer is a common disease and is a leading cause of death in many countries. The management of lung cancer is directed by an optimal staging of the tumour. Integrated positron emission tomography (PET)/computed tomography (CT) is an anatomo-metabolic imaging modality that has recently been introduced to clinical practice and combines two different techniques: CT, which provides very detailed anatomic information; and PET, which provides metabolic information. One of the advantages of PET/CT is the improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(58 citation statements)
references
References 55 publications
1
50
2
5
Order By: Relevance
“…5 When one considers that more than 200,000 new cases of non-small cell lung cancer (NSCLC) alone are diagnosed in the United States annually and up to 20% of these patients have adrenal gland lesions, minimally invasive urologists will increasingly be called on to evaluate and potentially operate on patients with suspicious PET/CT adrenal findings. [2][3][4] This review examines two cases of NSCLC with positive adrenal PET/CT, summarizes the existing literature, explains the possible causes for false-positive PET findings, and provides a treatment algorithm that may be helpful in PET/CT interpretation and in decision making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 When one considers that more than 200,000 new cases of non-small cell lung cancer (NSCLC) alone are diagnosed in the United States annually and up to 20% of these patients have adrenal gland lesions, minimally invasive urologists will increasingly be called on to evaluate and potentially operate on patients with suspicious PET/CT adrenal findings. [2][3][4] This review examines two cases of NSCLC with positive adrenal PET/CT, summarizes the existing literature, explains the possible causes for false-positive PET findings, and provides a treatment algorithm that may be helpful in PET/CT interpretation and in decision making.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] These recommendations have evolved because of FDG-PET/CT's ability to integrate both anatomic and functional assessments of potential metastasis, improving not only staging accuracy but also surveillance and restaging accuracy for a variety of cancer types. 5 When one considers that more than 200,000 new cases of non-small cell lung cancer (NSCLC) alone are diagnosed in the United States annually and up to 20% of these patients have adrenal gland lesions, minimally invasive urologists will increasingly be called on to evaluate and potentially operate on patients with suspicious PET/CT adrenal findings.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Developing regions, particularly high tuberculosis (TB)-endemic areas, face the potential challenge of interpreting PET-CT images as false positive in TB-involved lymph nodes. [2,5,9,10] The effect of TB on PET-CT staging of NSCLC has previously been investigated in areas with an incidence of TB of approximately 73/100 000 population. [5,11,12] Two studies from Korea showed that the sensitivity (75% and 46%, respectively) and PPV (27% and 72%) of PET-CT were adversely affected, but that a high specificity (85% and 98%) and NPV (98% in both studies) were maintained, especially when calcification and attenuation of nodes on CT was taken into account.…”
mentioning
confidence: 99%
“…[1] Non-small-cell lung cancer (NSCLC) comprises 75 -80% of lung cancer cases. [2] Determining mediastinal lymph node involvement is fundamental in the staging of NSCLC and has been shown to have prognostic significance. [3] The node (N) stage determines the treatment strategy, as patients with N2 lymph node metastasis are considered inoperable and only selected patients with this stage are eligible for chemotherapy and/or radiotherapy with curative intent.…”
mentioning
confidence: 99%
See 1 more Smart Citation